Brain stimulation used as biofeedback in neuronal activation of the temporal lobe area in autistic children - Vernon Furtado da Silva; Mauricio Rocha Calomeni; Rodolfo Alkmim Moreira Nunes; Carlos Elias Pimentel; Gabriela Paes Martins; Patrícia da Cruz Araruna Oliveira; Patrícia Bagno Silva; Alair Pedro Ribeiro de Souza e Silva (Arquivos de Neuro-Psiquiatria)
ABSTRACT This study focused upon the functional capacity of mirror neurons in autistic children. 30 individuals, 10 carriers of the autistic syndrome (GCA), 10 with intellectual impairments (GDI), and 10 non-autistics (GCN) had registered eletroencephalogram from the brain area theoretically related to mirror neurons. Data collection procedure occurred prior to brain stimulation and after the stimulation session. During the second session, participants had to alternately process figures evoking neutral, happy, and/or sorrowful feelings. Results proved that, for all groups, the stimulation process in fact produced additional activation in the neural area under study. The level of activation was related to the format of emotional stimuli and the likelihood of boosting such stimuli. Since the increase of activation occurred in a model similar to the one observed for the control group, we may suggest that the difficulty people with autism have at expressing emotions is not due to nonexistence of mirror neurons.